Spiral Concentration for Cleaning Fines from Major Brazilian Coalfields - C. H. Sampaio (Society for Mining, Metallurgy & Exploration, 1995)
The effectiveness of modem spirals in the processing of fines from Brazilian coals is assessed and discussed. Coals representing the four major coalfields in Brazil have been cleaned in Reichert LD 9 spirals in pilot and industrial plants and performance results are here presented. Normalized distribution curves for all equipment and splitters are presented and were modeled using an empirical model. These data have been compared with those for shaking tables and water-only cyclones (WOC), and it has been observed that, in the size interval investigated, spirals have indeed superior accuracy than WOC and comparative performance to tables. By analyzing experimental as well as simulation results it could be observed that although limited by the poor liberation characteristics of most Brazilian coals, significant ash and sulfur removal could be achieved using spirals.